Diaphragmatic Injuries in Patients with Penetrating Thoracoabdominal Injuries without Shock or Acute Abdomen at Admission - Alejandro González-Muñoz; Laura Otálora González; María Paula Fontecha Pinzón; Angela Cristina Ríos Cadavid; Cristina Judith Padilla Herrera; Danny Michell Conde Monroy; José Gabriel Rodríguez-Narváez; David Rene Rodriguez Lima (Journal of Emergencies, Trauma and Shock)
Introduction: Penetrating thoracoabdominal injuries (PTAIs) are associated with diaphragmatic injuries and subsequent complications. This study aimed to describe the prevalence of diaphragmatic injuries in patients with PTAI without signs of shock or acute abdomen at admission. Methods: A cross-sectional, single-centered study was conducted in Bogotá, Colombia. The study included all patients with PTAI who underwent surgical exploration and were admitted without signs of shock or acute abdomen, between January 2019 and August 2021. Indications for surgical exploration included presence of left thoracoabdominal wound, hemo- or pneumothorax in presurgical imaging, abdominal pain, hypotension, or anemia. Results: A total of 284 patients were included in the final analysis. The median age was 29 years (interquartile range: 22–33), with 269 (94.7%) patients being males. Out of these, 268 (94.3%) patients experienced stabbing as the mechanism of injury. The prevalence of diaphragmatic injuries diagnosed during surgical exploration was 15.1% (43 patients). There were 183 patients with left-sided PTAI and 115 patients with right-sided PTAI. The prevalence of the right diaphragmatic injury was 25.2% (29 patients), while for left diaphragmatic injury, it was 8.1% (15 patients). Only one patient presented with bilateral diaphragmatic injury. Conclusions: The prevalence of diaphragmatic injuries in patients with PTAI, without signs of shock or acute abdomen upon admission, was 15.1%. However, the prevalence was 25.2% in the right PTAI and 8.1% in the left PTAI. These findings suggest that surgical exploration of the diaphragm in cases of PTAI should be performed regardless of the side of the wound.